Pengaruh Kepuasan Pelanggan, Citra Merek, Harga Dan Kualitas Produk Terhadap Loyalitas Pelanggan Pada Handphone Xiaomi Di Yogyakarta - Listyawati, Indri Hastuti (Universitas Muhammadiyah Yogyakarta, 2018)
The purpose of this study is to determine the effect of customer satisfaction, brand image, price, and product quality on consumer loyalty decisions on Xiaomi mobile phone in Yogyakarta. The population in this research is the user of Xiaomi mobile phone in Yogyakarta. While the sample in this study is the user of Xiaomi note 4. This study is using the primary data, the data obtained directly from the source. Primary data in this study is the answer from consumers who become respondents. In this study researcher used survey methods. Survey method is a research method implemented by taking samples from a population and using questionnaires. This study uses convenience sampling technique that is because of the ease of sampling. The results showed that the customer satisfaction, price, brand image and product quality significantly influence the customer loyalty on Xiaomi note 4 in Yogyakarta. These results indicate that customer satisfaction, price, brand image and product quality can create customer loyalty.